Components and Development of Tourism in South Lembar Mangrove Forest Ecotourism - Qoula Sadida; Jasmine C. U. Bachtiar (Media for Empowerment, Mobilization, and Innovation in Research & Community, 2025)
Tourism, as defined by the World Tourism Organization (WTO), involves activities where individuals travel or stay outside their usual environment for purposes such as leisure or business, for less than one year. Ecotourism emphasizes the use of natural tourism potential for conservation and development while minimizing ecological and cultural harm. This study explores sustainable mangrove ecotourism development in South Lembar, aiming to involve the community and support local economic growth. The study employs a qualitative descriptive method, collecting data through observation, interviews, documentation, and literature. The focus is on the local community as the subject and tourism potential as the object. Primary data is gathered from field surveys conducted on September 21, 2024, while secondary data is derived from academic references. South Lembar Mangrove Forest Ecotourism, managed by the local community, attracts domestic visitors with its natural appeal, including mangrove forests, river estuaries, and scenic sunsets. Advantages include diverse flora and fauna habitats and facilities like gazebos and small boats. However, challenges persist, such as poor road conditions, under-maintained infrastructure, non-permanent parking areas, and limited hygiene facilities. Although ecotourism principles are not yet fully implemented, the site has significant potential. Improved government and community support could enhance accessibility, infrastructure, and visitor experience, attracting more tourists and benefiting the local economy. Sustainable development of this destination can promote ecological conservation while fostering economic and social well-being.